IMPLEMENTASI PRINSIP TATA KELOLA PEMERINTAHAN TERHADAP KUALITAS PELAYANAN PUBLIK DI KOTA KENDARI PROVINSI SULAWESI TENGGARA - Muhammad Amir; Adrian Tawai; Muhammad Yusuf (Halu Oleo University, 2023)
The aim of this research is to determine the implementation of governance principles on the quality of public services in Kendari City, Southeast Sulawesi Province. Qualitative descriptive research methodology which includes observation, interviews and documentation was used in this research. Data analysis uses descriptive interactive according to Milles Huberman and Saldana. The findings of this research indicate that the application of good governance principles in improving the quality of public services, in terms of transparency, has not been fully realized, especially regarding access to service requirements that cannot be reached by all levels of society. Second, responsiveness in responding to needs is quite good, but completion in a timely manner is not appropriate due to the large number of taxpayers quantitatively. Third, a fair aspect in providing services has been implemented by giving priority to the community in a timely manner. Fourth, the effectiveness and efficiency of employees can be seen, with their efforts increasing their potential to improve services. Fifth, employee accountability through reprimanding and directing staff who commit negligence, but there are still staff who repeat this negligence and act not in accordance with the SOP.